Efficacy and safety of medical expulsion therapy for ureteral calculi: a systematic review and network meta-analysis. (December 2017) - Bao, Yige; Bian, Haiyang; Qiu, Shi; Huang, Chengyi; Liu, Liangren; Liu, Zhenhua; Yang, Lu; Wei, Qiang
Abstract: Background: The effectiveness of medical expulsive therapy for the non-invasive management of patients with ureteral calculi has been called into question. We aimed to evaluate the benefits and harms of various medical expulsive therapies using a systematic review and network meta-analysis. Methods: We incorporated both direct and indirect evidence from relevant trials. We searched PubMed, the Cochrane Library Central Register of Controlled Trials, Scopus, Embase, and the reference lists of relevant articles for randomised controlled trials published up to Oct 1, 2016, of medical expulsive therapy. The primary outcome was the proportion of participants who did not need further intervention for stone clearance within 4 weeks of randomisation, stone expulsion rate, stone expulsion time, and adverse events. We did pairwise meta-analyses by random effects model and network meta-analysis by Bayesian random effects model. We assessed the quality of evidence contributing to each network estimate using the GRADE framework. This study is registered with PROSPERO, number 42016051277. Findings: From a total of 1873 citations, 65 randomised trials with a total of 10 493 participants were included in this network meta-analysis. 14 strategies for medical expulsive therapy published between 2000 and 2016 were considered. Tamsulosin plus tadalafil (relative risk [RR] 7·31, 95% credible interval [CrI] 1·83–14·37), surface under the cumulative ranking curve [SUCRA], 0·90) was ranked the best, followed by alfuzosin (6·50, 3·50–12·2, SUCRA 0·81), tadalafil (6·39, 2·15–10·02, SUCRA 0·77), doxazosin (6·13, 3·50–11·5, SUCRA 0·75), and tamsulosin (5·89, 1·50–9·42, SUCRA 0·69) considering stone expulsion rate. Alfuzosin showed significant superiority over nifedipine (RR 6·19, 95% CrI 2·72–13·57) and ramsulosin (2·19, 1·18–4·04) in terms of stone expulsion rate. Tamsulosin plus tadalafil was significantly more effective than nifedipine (standardised mean difference [SMD] −0·89, 95 % CI −1·19 to −0·60), Tamsulosin (−2·36, −4·61 to −0·81), and placebo (SMD −3·20, −5·19 to −2·21) in terms of stone expulsion time. No significant difference between any group of medical expulsive therapy was found in terms of further intervention need for stone clearance and adverse events. Out results showed the same significance in the subgroup analysis of stone size (<5 mm vs >5 mm) and stone location (upper and lower ureteral). Interpretation: In adults with ureteral stones smaller than 10 mm in size, tamsulosin plus tadalafil and alfuzosin are safe and effective for expulsive therapy. Nevertheless, these results should be considered together with all known safety and economic information when selecting the strategy for individual patients. Head-to-head comparisons of medical expulsive therapy are limited, but still needed to confirm the findings. Funding: Prostate Cancer Foundation Young Investigator Award 2013, National Natural Science Foundation of China (81300627 and 81370855), and Programs from Science and Technology Department of Sichuan Province (2013SZ0006 and 2014JY0219).